Comparison of the Properties of Acellular Matrix from the Skins of Cod (Gadus morhua) and Tilapia (Oreochromis mossambicus) - Yu Liu; Zeyu Wei; Rui Duan; Ke Wang; Tianyue Xu; Binxian Mao; Junjie Zhang (Journal of Functional Biomaterials)
Acellular tissue matrices of fish skin origin are highly promising materials for tissue engineering due to their low biological risks and few religious restrictions. The main component of acellular fish skin matrices (AFSMs) is collagen, but collagen properties significantly differ between marine and freshwater fish. Although the characteristics of acellular matrices may vary, relevant reports about them are few. In this study, we used cod and tilapia fish skin as raw materials to prepare acellular matrices with low DNA content (≤50 ng/mg) and low endotoxin. They were denoted as C-AFSM (cod) and T-AFSM (tilapia) and had endotoxin removal rates of 92.47% and 96.73%, respectively. Their physicochemical properties, cytotoxicity, and wound healing effects were evaluated and compared. Scanning electron microscopy images showed that C-AFSM and T-AFSM had collagenous meshwork and high porosity. They also did not induce skin irritations. Their proliferation rates on mouse fibroblasts at 36 h were 192.21% ± 33.25% and 162.89% ± 36.47%, respectively. The wound healing effect of C-AFSM was faster than that of T-AFSM group (7 and 14 days: 45.3% ± 5.99% and 93.77% ± 1.58% for C-AFSM and 39.7% ± 2.84% and 93.35% ± 1.1% for T-AFSM, respectively). Therefore, the two acellular fish skin matrices can be used as tissue-engineering materials for wound repair, with C-AFSM being more effective than T-AFSM.